Pengaruh Flash Sale dan Persepsi Harga terhadap Keputusan Pembelian Skincare Skintific di TikTok Shop pada Generasi Z di Kabupaten Tasikmalaya - Reni Rohaeti; Aditia Abdurachman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2026)
The rapid growth of skincare sales on TikTok Shop, including the Skintific brand, highlights the importance of understanding the factors influencing Generation Z's purchase decisions, particularly in Tasikmalaya Regency, where consumers tend to be selective toward flash sale promotions and often perceive prices as not fully proportionate to product benefits. This study aims to analyze the influence of flash sale and price perception on Skintific skincare purchase decisions on TikTok Shop among Generation Z in Tasikmalaya Regency. A quantitative associative approach was employed, with data collected from 100 respondents through structured questionnaires and analyzed using SPSS version 25, encompassing validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results reveal that flash sale has a positive and significant effect on purchase decisions, with the calculated t-value exceeding the t-table at a significance level below 0.05. Price perception also shows a positive and significant effect on purchase decisions, with a greater influence than flash sale. Collectively, both variables explain a substantial proportion of the variation in purchase decisions. These findings imply that digital marketers need to optimize flash sale strategies and build positive price perceptions to more effectively drive Generation Z consumers' purchase decisions.